2020
DOI: 10.1007/s41247-020-00081-4
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Oil Cycle Dynamics to Design the Future Economy

Abstract: In this work, we make the ansatz that economic production is reduced to the energy made available to the economy. In (Illig and Schindler, BioPhys Econ Resour Qual 2(1):1, 2017) the price of oil was expressed as a function of the size of the economy, the cost share of oil, and the quantity of oil extracted. We clarify assumptions needed to use this explicit price equation to study prices. Using the current extraction rate, the previous year's extraction rate, and interest rates of the Federal Reserve we use li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Halicioglu [40] and Magazzino [41] highlight that the real GDP drives energy consumption and CO 2 emissions, findings validated by recent studies [42][43][44][45]. Climate change and environmental degradation impact economic sustainability [3,[46][47][48], generating potential negative implications of climate change on economic activity and affecting the population welfare. Managing climate risks at the EU level necessitates proactive management based on identifying relationships between economic and green performances, GHG emissions reduction, and forest resource coverage-the most significant CO 2 catcher [49].…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 74%
See 1 more Smart Citation
“…Halicioglu [40] and Magazzino [41] highlight that the real GDP drives energy consumption and CO 2 emissions, findings validated by recent studies [42][43][44][45]. Climate change and environmental degradation impact economic sustainability [3,[46][47][48], generating potential negative implications of climate change on economic activity and affecting the population welfare. Managing climate risks at the EU level necessitates proactive management based on identifying relationships between economic and green performances, GHG emissions reduction, and forest resource coverage-the most significant CO 2 catcher [49].…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 74%
“…The repercussions of climate change and environmental degradation (including GHG growth) extend to economic sustainability [3,[46][47][48], with potential adverse effects on economic activity and overall population welfare.…”
Section: Forestrymentioning
confidence: 99%
“…Demand side shocks, which are most important, occur due to increases in population growth and household income, dollar depreciation, and an increase in biofuel production such as ethanol (Wang et al 2018 ; Lima et al 2019 ). Garcia et al ( 2020 ) showed that the COVID-19 pandemic negatively affected international crude oil demand and reduced prices. The rise in biofuel production is responsible for the rise in the prices of agricultural commodities (Paris 2018 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It should be noted that Sect. Resources Produced Jointly with Fossil Resources only studies two fossil fuel supply scenarios and that many other trajectories are possible, for example if affordability of fossil fuels change (Garcia et al 2020).…”
Section: Uncertainties With Estimating Future Stocks Potential Flows and Recovered Flowsmentioning
confidence: 99%